2017
DOI: 10.11608/sgnj.2017.22.027
|View full text |Cite
|
Sign up to set email alerts
|

Zadovoljstvo poslom kod medicinskih sestara i tehničara koji rade u operacijskim salama i kirurškim odjelima Kliničkog bolničkog centra Rijeka Job satisfaction within the nurses and technicians who work in operating and surgical wards in University Hospital Centre Rijeka

Abstract: Zadovoljstvo poslom kod medicinskih sestara i tehničara koji rade u operacijskim salama i kirurškim odjelima Kliničkog bolničkog centra RijekaJob satisfaction within the nurses and technicians who work in operating and surgical wards in University Hospital Centre Rijeka Marija Spevan 1,2,3 , Sandra Bošković 1,2,3 , Radoslav Kosić 1,2,3 1,2,3 Klinički bolnički centar Rijeka, Klinika za kirurgiju, Krešimirova 52, 51 000 Rijeka, Hrvatska RESEARCH / ISTRAŽIVANJEORIGINALNI ČLANAK / ORIGINAL ARTICLE SG/NJ 2017;22:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The average age of the respondents was 37.48 years, and the majority of respondents had completed secondary medical education (70.6%), worked in shifts (81.7%), and had completed more than 20 years of service (40.4%). Similar population results for employed nurses have been published in other Croatian studies (Smokrović et al, 2019;Spevan et al, 2017). Therefore, we can say that in terms of the basic demographic characteristics of the sample, our respondents represent the nursing population of Croatia relatively well.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The average age of the respondents was 37.48 years, and the majority of respondents had completed secondary medical education (70.6%), worked in shifts (81.7%), and had completed more than 20 years of service (40.4%). Similar population results for employed nurses have been published in other Croatian studies (Smokrović et al, 2019;Spevan et al, 2017). Therefore, we can say that in terms of the basic demographic characteristics of the sample, our respondents represent the nursing population of Croatia relatively well.…”
Section: Discussionsupporting
confidence: 85%
“…Data relating to job satisfaction indicated that most employees, [72 (66%)], were satisfied with their job; with only eight respondents (7.4%) expressing dissatisfaction. Research conducted at the University Hospital of Croatia, where 126 nurses worked in operating rooms or the surgery department, found similar results for job satisfaction (Spevan et al, 2017), as did another study conducted at the Croatian University Hospital (Barać et al, 2018). Smokrović et al (2019) noted that besides personal traits and working environment, the factor that influenced job satisfaction in nurses was their work motivation.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation